The Hsp90 Chaperone Network Modulates Candida Virulence Traits. Issue 10 (October 2017) - O'Meara, Teresa R.; Robbins, Nicole; Cowen, Leah E.
Abstract : Hsp90 is a conserved molecular chaperone that facilitates the folding and function of client proteins. Hsp90 function is dynamically regulated by interactions with co-chaperones and by post-translational modifications. In the fungal pathogen Candida albicans, Hsp90 enables drug resistance and virulence by stabilizing diverse signal transducers. Here, we review studies that have unveiled regulators of Hsp90 function, as well as downstream effectors that govern the key virulence traits of morphogenesis and drug resistance. We highlight recent work mapping the Hsp90 genetic network in C. albicans under diverse environmental conditions, and how these interactions provide insight into circuitry important for drug resistance, morphogenesis, and virulence. Ultimately, elucidating the Hsp90 chaperone network will aid in the development of therapeutics to treat fungal disease. Trends: The Candia albicans Hsp90 chaperone network is environmentally contingent, with a vast majority of genetic interactors important for growth only under a specific environmental condition. Gene products displaying a genetic interaction with Hsp90 in diverse conditions are more likely to regulate Hsp90 levels or function. Hsp90 function can be modulated transcriptionally, post-translationally, by co-chaperones, and by overwhelming its functional capacity in response to diverse cellular stressors. Chemical genomic screens mapping Hsp90 interactors unveil novel circuitry governing morphogenesis, a key virulence trait. Distinct cellular forms, including the formation of C. albicans biofilms, dramatically alter the Hsp90 interaction network.